An Organizational Legitimacy In Managing The Hajj Funds - Susi Indriani Indriani; Ahmad Zamri; Hairul Azlan Annuar (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study focuses on BPKH processes in achieving organizational legitimacy. The way stakeholders see the validity of BPKH aligns with how organizations try to gain credibility by passing on accountability actions. The pilot study explores the account-giving situation from the meaning of accountability between BPKH and its stakeholders as the reason to gain legitimacy. The perception in this pilot study explains what they see, hear, and feel about BPKH as an organization and the shared information. The way that BPKH is seen by its stakeholders is in line with the goal of transferring accountability measures, which is a goal of organizational legitimacy. A pilot study is one of the methodological approaches that may be utilized to improve the reliability and validity of research. Description of textual data in qualitative research using the inductive approach.The pilot study found that BPKH showed a significant improvement in delivering information to the public compared to the previous fund holder (MORA). The process legitimacy can be seen from the circulation of information inside a system. These modifications are the designed system and the structured formulation of the information to achieve legitimacy through an organization's accountability. Keywords: organizational legitimacy, accountability, hajj funds, pilot study